Dinamika Status Santri-Siswa di Madrasah Aliyah Al Islamiyah Danawarih Balapulang Tegal - Ayu Sofiani; Ahmad Ziyaurrohman; Puji Astuti; Siti Amanah Mahiroh; Siti Faikhatul Janah (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2023)
The purpose of this study was to determine the Dynamics of Santri Status - Students at MA Al Islamiyah Danawarih Balapulang Tegal. The research method used descriptive qualitative, data collection through interviews, observation and documentation. The research paradigm is postpositivistic with data analysis of three models of Miles and Huberman, namely data reduction, data presentation and conclusion drawing. The results in this study are to determine the dynamics of the status of students (a santri who simultaneously attends formal school in a boarding school) at MA Al Islamiyah Danawarih. While the characteristics of santri - students at MA Al Islamiyah Danawarih are that all school residents are Muslim, wear uniforms or clothes that cover the aurat (sons squatting and daughters veiling), seating between boys and girls is separated, applying high discipline, reading asmaul husna and prayers at the beginning of lessons routinely in the morning before starting lessons, Diniyah school in the afternoon after formal school.